Auditoría de gestión del talento humano en el gobierno autónomo descentralizado, cantón San Miguel, provincia Bolívar, periodo diciembre 2014 - julio 2015 - Lombeida Prado, Janneth Estefanía (2015)
This research justifies its practice as it will contribute to the development of the Autonomous Government Decentralized Canton San Miguel de Bolivar considering it as a model of immediate solution conducting an audit, to promote efficiency and effectiveness in the conduct of its operations, providing a reasonable level of safety, cost reduction and simplification of tasks, through a Plan of Audit Human Resource Management to meet the goals and objectives formulated in the short, medium and long term; also allow you to evaluate your weaknesses, establish potential risks facing the administration as a process carried out, the reliability of information, strengthen confidence in compliance with applicable laws and regulations. To summarize this research work will help the Decentralized Autonomous Government of the Canton San Miguel de Bolivar to get where he wants to go and avoid dangers, surprises along the way, assessing the risks to mitigate the impact; immediately adopt criteria that will improve the administrative systems, internal control and management of any operational aspect of the entity to be transformed into opportunities, strategies conducive to development, ability, integrity and stability of the institution through an examination special Human Resource Management, focusing on the activities carried out. By applying the Audit Plan Human Resource Management at the Autonomous Government Decentralized Canton San Miguel de Bolivar in 2015, we will be helping to identify gaps, weaknesses or abnormalities that may arise in the activities that are carried out by the public servants and how performance influences the level of the same in the optimal fulfillment of corporate goals. To start with the Audit Management Plan have as Phase I preliminary analysis and diagnosis history where vision is determined legal aspects as well as strategic planning and finally administrative procedure manual processes. Then we give grounds to phase II which is the specific planning by which we establish a close relationship between the professional and the institution is the municipal GAD, making an outline of the situation of the entity, organization, internal controls and strategies. Then we proceed to Phase III which is the execution that is the center of the Auditing itself as this is where all the necessary examinations in which use of the necessary techniques is also made for the requesting information are made to the livelihood of work. PHASE IV Report of results where two chapters focus on the introduction and focus of the audit will also be addressed. As a final part of the Phase V would follow where we will control if they have not been complied with or the recommendations for each case. Importantly for success an organization must take control of all the institutions involved in municipal activities to be carried out simply and efficiently.